Severity and mortality of COVID-19 among people with disabilities: protocol for a systematic review and meta-analysis - Abay Woday Tadesse; Abubeker Alebachew Seid; Aragaw Asfaw Hasen (BMJ Open)
Introduction As the COVID-19 pandemic and the subsequent global healthcare crisis continue, people with disabilities may face greater health risks than their non-disabled peers. This systematic review and meta-analysis aims to determine the severity and mortality of COVID-19 among people with different types of disabilities.Methods and analysis We will search PubMed, HINARI, ScienceDirect, PEDro and Cochrane Library databases. Grey literature search will also be conducted on MedRxiv and Google Scholar. Searches will be without date restrictions. Cohort, case-control and cross-sectional studies assessing the severity and mortality of COVID-19 among people with disabilities will be included. Only full-text studies in the English language will be included. The outcomes of interest include the risk of COVID-19 infection, rate of hospitalisation, severity, hospital stay, mortality and others variables where data are available. Two reviewers will extract data and perform risk of bias assessment independently. The Newcastle-Ottawa Scale will be used to assess risk of bias. Review Manager V.5.4 and Stata V.16.0 software will be used for statistical analysis. Heterogeneity will be analysed using I² statistics. Pooled OR with 95% CI will be used to calculate the pooled results for outcome variables.Ethics and dissemination Ethical approval and informed consent are not required as this is a systematic review of existing publications. The final results will be published in a peer reviewed journal and presented at national and international conferences.PROSPERO registration number CRD42022306361.